Procrear en la norma: cómo las parejas infértiles judías y musulmanas negocian con las técnicas de reproducción médicamente asistida (RMA) = Procreating is the norm : or how infertile Jewish and Muslim couples deal with new reproductive techniques - Fassatoui, Omar (Ciencias sociales y religión, 2019)
As with other couples confronted with infertility, religious couples seeksolutions within the three monotheisms which undeniably incentivize procreation. With this aim, they turn to techniques of medically assisted reproduction (new reproductive techniques). Investigating their desire to conceive a child, and comparing this desire to that of less religious couples, we can observe a unique will to abide by certain standards. They certainly want to have a child but it has to be in accordance with the religious rules. On this basis, these couples may reject some existing and effective techniques which would be incompatible with the rules they abide by. Having explored this issue in Judaism and Islam in the Mediterranean, I would like to explain during the working group how the will to conform to certain rules can condition an entire health system especially if the will is at the state level (in the case of state religion or the official religion of the state). We will also see, through concrete examples of Jewish and Muslim contexts, how the religious standards can reduce or expand the range of techniques that infertile couples can engage in. We will also explore how the desire to conform to the religious standards for this particular issue creates original positions when it comes to accommodating to those standards. We will also examine the role of globalization and the internet in this regard, and how religiously approved advanced medicines are constructed.